Farmers field day to evaluate salt-tolerant rice varieties - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
143 participants from the villages of Gnngarampur, local government representatives, and staff members of the Cereal Systems Initiative for South Asia (CSISA)-Khulna Hub attended a field day for participatory evaluation by farmers of salt-tolerant aman rice varieties at Khulna District (Bangladesh) on 24 November 2011. Participants cast their votes for the best and the worst varieties according to their own preference.